Growth Differentiation Factor GDF 15 (“Protein of Senility”) under Conditions of Oxidative Stress and Intermittent Nocturnal Hypoxia in Patients with Sleep Apnea Syndrome - Madaeva, I. M.; Kurashova, N. A.; Titova, E. V.; Berdina, O. N.; Sholokhov, L. F.; Semenova, N. V.; Kolesnikov, S. I.; Kolesnikova, L. I. (Advances in gerontology, 2024)
The main pathophysiological triggers of obstructive sleep apnea (OSA) syndrome are oxidative stress and hypoxia. These factors cause cellular and molecular disorders that characterize the aging process. The fact that the blood content of the differentiating protein GDF-15 (the “protein of senility”) increases with age, which was revealed by a number of researchers, arouses interest in its assessment in patients with OSA. Thus, the purpose of this study is to evaluate changes in the content of GDF-15 under conditions of oxidative stress and intermittent nocturnal hypoxia with normalization of the nocturnal oxygen gradient in patients with OSA. The study involves 30 men aged 45–55 years with moderate OSA (main group, MG1) and 35 men of the same age without OSA (control group, CG). The MG1 patients are prescribed aРАР therapy (automatic positive airway pressure) during sleep for 6 months. These patients after treatment make up the second main group, MG2. Blood is taken from all the subjects in the morning to determine the content of lipid-peroxidation products and components of antioxidant defense (LPO-AOD) and GDF-15. The following methods are used to evaluate the results: questionnaires, polysomnographic monitoring, spectrometric and radioimmunoassay methods, and statistical analysis. According to the results, an imbalance of the LPO-AOD system with the predominance of oxidation processes in MG1 is revealed demonstrating the coefficient of oxidative stress, which statistically significantly decreases with the elimination of hypoxia and improvement of sleep structure. GDF-15 demonstrates significant differences between MG1 and CG patients with a predominance of content in the group of MG1 patients with OSA. In comparison with the indicators of MG2, no statistical differences are revealed.